An Etiology Report for Burns Caused by Korean Folk Remedies - Joo, Hong Sil; Kim, Hyun Been (Archives of Plastic Surgery, 2023)
Background In this modern era of science-based medicine, some people still accept folk remedies as an alternative form of medicine. However, misinformation and misuse of folk medicines can result in dangerous complications. Among the possible complications of folk remedy use, this study focused on the clinical characteristics of burns caused by folk remedies.Methods We retrospectively reviewed the clinical records of patients who had been treated for burns caused by folk remedies from May 2015 to April 2022. Data were collected on patients' age and gender, type of folk remedy, reason for using the folk remedy, the severity of the burn, the number of wounds, lesion type, and type of treatment.Results We found 59 patients with burns due to folk remedies. Most were female (76.3%) and ≥ 60 years old (72.9%). The most common type of folk remedy was moxibustion (74.6%), followed by the use of glacial acetic acid (20.3%). The reasons for using folk remedies were arthralgia relief (39%), health improvement (18.6%), and treatment of tinea pedis (11.9%). Most patients had multiple wound sites and had burns that were considered severe, requiring surgical treatment (72.9%). The majority of lesions were on the lower extremity, including the foot.Conclusion This study described the risk of burns caused by folk remedies and the clinical characteristics of the wounds. The results emphasize the need for greater public awareness of the risk of burn injuries when using folk remedies.
Keywords: burns; folk remedies; glacial acid; moxibustion